The Influence Of Company Image And Product Marketing Strategy On Purchasing Decisions Of Regional Apparatus Organisations (Opd) Via E-Catalogue (Case Study At Pt Kreativ Niaga Mandiri) - Inka Nabela; Anzori Anzori; M Rahman Febliansa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of corporate image and marketing strategy on purchasing decisions for goods and services through the local e-catalog at PT Kreativ Niaga Mandiri. Government procurement of goods and services, regulated under LKPP Regulation No. 9 of 2021, provides a local e-catalog platform that facilitates effective fulfillment of needs by Government Agencies (OPD). In this study, a path analysis model is applied to understand the relationship between independent variables (corporate image and marketing strategy) and the dependent variable (purchase decision) using a quantitative causality approach. Data were collected via an online survey using a closed questionnaire distributed to 72 OPD respondents through Google Forms. The findings indicate that both corporate image and marketing strategy have a significant and simultaneous effect on purchasing decisions. A positive corporate image enhances consumer trust, while an effective marketing strategy attracts purchasing interest. Based on these findings, it is recommended that PT Kreativ Niaga Mandiri strengthen its corporate image, improve service quality, and optimize digital marketing strategies to maintain the company's relevance and competitiveness.